Development of an immunofluorescence test for the serodiagnosis of herpes zoster ophthalmicus. Issue 6 (June 1986) - Walpita, P.; Darougar, S.; Marsh, R. J.; Cooper, M.
Abstract : An indirect immunofluorescence test has been developed and evaluated for the serodiagnosis of herpes zoster ophthalmicus (HZO) by the detection of antivaricella zoster virus (VZV) antibody. The results show that, in patients with HZO, anti-VZV IgG antibody titre usually rises rapidly after onset. One hundred and seven of the 134 sera (80%) from patients with a clinical diagnosis of HZO had an anti-VZV IgG titre of greater than or equal to 256, and IgM antibody at a level of 1 in 8 was present in six of them. In comparison only two of the 216 sera (1%) from patients with a clinical diagnosis of ocular infections other than those caused by VZV had such IgG titres. It was concluded that, on the basis of results of a single sample of serum, it is possible to make a provisional diagnosis of HZO with a high degree of confidence.